How Do Junior High School Students Solve Problems in Non-Routine Mathematics Problems - Zulkipli, Zulkipli; Saidah, Muthiah as (Angstrom Centre of Education, 2024)
One indicator of success in learning mathematics is problem solving ability. There are two types of mathematics questions that are generally known, namely routine and non-routine questions. Based on these reasons, the question arises of how junior high school students represent mathematically in solving non-routine mathematics problems. This research uses a qualitative approach with descriptive research type. Data was collected using research instruments in the form of non-routine mathematics test instruments to measure students' mathematical representation abilities in problem solving. Then the subject will be interviewed about how he represents the answer to the question. The data will be analyzed by researchers using the Miles, Huberman, Saldana model to describe and provide mathematical problem solving skills. There are findings that need attention, namely the existence of differences in variations in problem solving. This can happen because students have different mathematical interpretation and representation abilities.